Aspiration Pneumonitis with Nasal Liquorrhea. Literature Review - E. V. Shelesko; O. I. Sharipov; N. A. Chernikova; O. N. Ershova; P. L. Kalinin; D. N. Zinkevich (Архивъ внутренней медицины)
Damage to the meninges in combination with the presence of a defect in the bone structures of the base of the skull and the formation of communication with the nasal cavity or paranasal sinuses are necessary conditions for nasal liquorrhea. There are a number of complications of nasal liquorrhea of various origins: infectious (meningitis, brain abscess), pneumocephalus, aspiration pneumonitis and gastritis. A review of the literature related to aspiration pneumonitis in nasal liquorrhea has been carried out. 4 articles were selected with descriptions of 9 cases. The analysis of demographic indicators of patients, clinical data, treatment characteristics was carried out. Based on the analysis of the literature, aspiration pneumonitis is a rare complication of nasal liquorrhea. For differential diagnosis with other types of pneumonitis, it is necessary to rely on additional clinical data, such as unilateral discharge of clear fluid from the nose when tilting the head, worsening of the condition and intensification of symptoms in a horizontal position, absence of systemic inflammatory response syndrome, ineffectiveness of antibiotic therapy, recurrent the nature of the flow. Antibiotic therapy does not cure the patient from pneumonitis. For the treatment of this pathology, it is first of all necessary to eliminate the cause of aspiration — to perform plastic surgery of the skull base defect in the absence of contraindications from the side of anesthetic aid.